Large-area reduced graphene oxide thin film with excellent thermal conductivity and electromagnetic interference shielding effectiveness - Kumar, Pradip; Shahzad, Faisal; Yu, Seunggun; Hong, Soon Man; Kim, Yoon-Hyun; Koo, Chong Min (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In this work, we fabricated reduced large-area graphene oxide (rLGO) with maximum surface area of 1592 mu m(2) through a cost-effective chemical reduction process at low temperature. The product revealed large electrical conductivity of 243 +/- 12 S cm(-1) and thermal conductivity of 1390 +/- 65 W m(-1) K-1, values much superior to those of a conventional reduced small-area graphene oxide (with electrical conductivity of 152 +/- 7.5 S cm(-1) and thermal conductivity of 900 +/- 45 W m(-1) K-1). The rLGO thin film also exhibited not only excellent stiffness and flexibility with Young's modulus of 6.3 GPa and tensile strength of 77.7 MPa, but also an efficient electromagnetic interference (EMI) shielding effectiveness of similar to 20 dB at 1 GHz. The excellent performance of rLGO is attributed to the fact that the larger area LGO sheets include much fewer defects that are mostly caused by the damage of graphene sp(2) structure around edge boundaries, resulting in large electrical conductivity. The manufacturing process of rLGO is an economical and facile approach for the large scale production of highly thermally conducting graphene thin films with efficient EMI shielding properties, greatly desirable for future portable electronic devices. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: COMPOSITE; PAPER; FABRICATION; LIGHTWEIGHT; TRANSPORT; SHEETS